Effect of heavy metals on the performance and bacterial profiles of activated sludge in a semi-continuous reactor. (February 2020) - Bhat, Sartaj Ahmad; Cui, Guangyu; Li, Wenjiao; Wei, Yongfen; Li, Fusheng
Abstract: Heavy metals are toxic to microorganisms at specific concentrations and can have a serious effect on the efficiency of biological wastewater treatment plants. The wastewater treatment performance and bacterial communities of activated sludge were investigated at different heavy metal concentrations (0.1–10 mg L −1 for Cd(II), Pb(II) and 1–100 mg L −1 for Cu(II)) in a well-controlled semi-continuous reactor in 30 d period. Glucose was added once every 8 h as the carbon source throughout the experiment. The heavy metal toxicity was related to chemical oxygen demand (COD), total organic carbon (TOC), three-dimensional fluorescence excitation-emission matrix (EEM) spectroscopy, bacterial activity and community composition. The first-order consumption rate for glucose showed that the activity was decreasing in comparison to the control. The COD removal efficiency was also decreased from 87% to 26% in all the reactors under different heavy metal concentrations treatment. The PCR-DGGE and sequencing results revealed that the bacterial diversity showed evident variations under heavy metal stress owing to the potential toxicity of heavy metals. At the genus level, Pedobacter steynii and Flavobacterium, were only tolerant to Cu(II) at 100 mg L −1, while Rhodanobacter thiooxydans resisted to all heavy metal concentrations except Cu(II) 100 mg L −1 . Cluster analysis and Principal component analysis (PCA) revealed that the microbial community in Cu(II) was different from the sludge samples treated with Cd(II) and Pb(II) concentrations. The study indicated that it is necessary to identify the metal tolerant species of bacteria for maintaining good performance of biological wastewater treatment plants. Graphical abstract: Image 1 Highlights: Effect of Cd(II), Pb(II) and Cu(II) on performance and bacterial communities of activated sludge were analyzed. COD removal efficiency decreased from 87% to 26% under different heavy metal concentrations. Shannon index was lower in higher concentrations of heavy metals as compared to lower concentrations. PCA also revealed clearly the differences between bacterial communities exposed to Cu(II) and Cd(II)/Pb(II).